An appraisal analysis of judgements used in shangri-la dialogues - Lê,Đặng Thùy Trang (ĐHĐN., 2015)
Appraisal theory is a theory belonging to the framework of Systemic Functional Linguistics developed over the past half century by Michael Halliday. This theory includes three divisions: Engagement, Attitude and Graduation. This study focused on a sub-system of Attitude, which is Judgement. The aim of the study is to investigate the judgements used in Shangri-la Dialogues in the year of 2004 to 2014. The findings of the study will increase knowledge and effective use of the judgement to Vietnamese learners of English. In order to obtain this aim, qualitative methods are taken into account. This research pays attention to the investigation into syntactic, semantic and pragmatic features of Judgement values. Besides, the performance of explicit and implicit judgement is also analyzed. The research data are collected from speeches delivered by politicians in Shangri-la Dialogues since the year 2004 to 2014